Efektivitas Media Pembelajaran Monopoli Berbasis Assure Terhadap Kemampuan Berpikir Kritis Peserta Didik - Nora Pramartasari; Rini Rita T. Marpaung; Arwin Achmad (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2018)
This research aim was to know the effectiveness of the monopoly learning media based ASSURE  in increasing students critical thinking of the second grade in SHS. The design used was a pretest-posttest not equivalent. The research samples were the students of MIA I and MIA III amounted of 65 students that were selected through purposive sampling technique. The data of this research were qualitative and quantitative. Qualitative data were average value of students critical thinking ability were based on the instrument and then analyzed descriptively. Quantitative data were obtained from N-Gain, average value of the pretest, posttest, and then analyzed statistically using test 0.05 confidence level in the U. The results showed that the students in experiments class have average achievement score in the critical thinking with the category "very good" while the catagory of control class is "less". The Improvement of the learning outcome from the experiment class was higher than the class of the control with an average value of gain (2,815±44.67). Thus, monopoly based learning media ASSURE was effective in increasing students critical thinking.Penelitian ini bertujuan mengetahui efektivitas media pembelajaran monopoli berbasis ASSURE dalam peningkatan berpikir kritis peserta didik kelas XI MIA.Desain yang digunakan dalam penelitian ini adalah pretest-posttest tak ekuivalen. Sampel penelitian adalah peserta didik kelas XI MIA I dan XI MIA III berjumlah 65 peserta didik  dan dipilih melalui teknik purposive sampling. Data berupa rata-rata nilai kemampuan berpikir kritis peserta didik yang diperoleh dari instrument kemampuan berpikir kritis lalu dianalisis secara deskriptif. Data hasil belajar diperoleh dari N-Gain, rata-rata nilai pretest, dan posttest, lalu dianalisis secara statistik menggunakan uji U pada taraf kepercayaan 0,05.Hasil penelitian menunjukkan bahwa peserta didik kelas eksperimen memiliki pencapaian skor berpikir kritis dengan kategori “sangat baik” sedangkan kelas kontrol ialah “kurang”. Kata kunci: assure, berpikir kritis, media monopoli, peserta didik